2018
DOI: 10.1103/physrevlett.120.164503
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Chained Turbulence in Actively Driven Flows on Spheres

Abstract: Recent experiments demonstrate the importance of substrate curvature for actively forced fluid dynamics. Yet, the covariant formulation and analysis of continuum models for nonequilibrium flows on curved surfaces still poses theoretical challenges. Here, we introduce and study a generalized covariant Navier-Stokes model for fluid flows driven by active stresses in nonplanar geometries. The analytical tractability of the theory is demonstrated through exact stationary solutions for the case of a spherical bubbl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 73 publications
1
29
0
Order By: Relevance
“…Figures 1(a-i) show snapshots of the statistically stationary state of the dimensionless relative vorticity ζτ for a range of R/Λ and Ωτ at t/τ = 15. For Ωτ = 0, we attain solutions akin to those obtained by Mickelin et al (2018) in the non-rotating case. When the dimensionless rotation rate of the sphere Ωτ is increased, the flow becomes zonalised, that is, the φ−variation in the vorticity field decreases.…”
Section: β−Plane Solutionssupporting
confidence: 51%
See 3 more Smart Citations
“…Figures 1(a-i) show snapshots of the statistically stationary state of the dimensionless relative vorticity ζτ for a range of R/Λ and Ωτ at t/τ = 15. For Ωτ = 0, we attain solutions akin to those obtained by Mickelin et al (2018) in the non-rotating case. When the dimensionless rotation rate of the sphere Ωτ is increased, the flow becomes zonalised, that is, the φ−variation in the vorticity field decreases.…”
Section: β−Plane Solutionssupporting
confidence: 51%
“…The dynamics at the poles are similar to those on a non-rotating flat plane and the non-inertial effects matter the most at the equator. method with a basis of spin-weighted spherical harmonics Vasil et al 2019); more details on the method can be found in the appendix of Mickelin et al (2018). A spectral expansion with a cut-off max = 256 was found to be sufficient to obtain converged solutions.…”
Section: β−Plane Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ellis [16] studied the effect of self-propulsion and curvature on the degree of defect unbinding. On the other hand, curvature can induce spontaneous flow and flocking [22][23][24][25][26][27][28]. Sanchez and coworkers [22] experimentally studied selfpropelled microtubule bundles on curved surfaces and reported the spontaneous generation of a streaming flow.…”
Section: Introductionmentioning
confidence: 99%